Floating wooden breakwater structures on beach at Nome, July 1905 - Nowell, Frank H., 1864-1950 (1905)
Caption on image: W.M. Johnston & Co. Floating Breakwater. Nome, Alaska, July 30th 1905. Length 150 ft., diam. 9 ft. Photo by F.H. Nowell, 4050 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number